2014
DOI: 10.1371/journal.pone.0114239
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Risk Factors and Consequences of Emergence Agitation in Adult Patients after Elective Craniotomy for Brain Tumor: A Prospective Cohort Study

Abstract: Emergence agitation is a frequent complication that can have serious consequences during recovery from general anesthesia. However, agitation has been poorly investigated in patients after craniotomy. In this prospective cohort study, adult patients were enrolled after elective craniotomy for brain tumor. The sedation-agitation scale was evaluated during the first 12 hours after surgery. Agitation developed in 35 of 123 patients (29%). Of the agitated patients, 28 (80%) were graded as very and dangerously agit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(70 citation statements)
references
References 30 publications
2
63
2
3
Order By: Relevance
“…All rights reserved. [2,3,8,18,21,[37][38][39][40][41][42][43][44] (Table 1). Here, we review some common risk factors and important issues presented in the literature.…”
Section: Proposed Risk Factors For Emergence Agitationmentioning
confidence: 99%
See 2 more Smart Citations
“…All rights reserved. [2,3,8,18,21,[37][38][39][40][41][42][43][44] (Table 1). Here, we review some common risk factors and important issues presented in the literature.…”
Section: Proposed Risk Factors For Emergence Agitationmentioning
confidence: 99%
“…Among these, although the RSAS and RASS have been commonly used and show high interrater reliability in adult intensive care unit patients [81,82], none of the scales have been validated in the operating room and/or the PACU. There have been few studies of EA in intensive care unit patients [37]; the majority of EA studies have been performed in PACUs or operating rooms [19,20,83].…”
Section: Assessment Tools For Emergence Agitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients after intracranial operations are more vulnerable to the stress resulting from emergence agitation during the recovery from general anaesthesia. 2 3 In our previous pilot study with 123 cases, 4 we found that the incidence of agitation was 29% in patients admitted to the intensive care unit (ICU) after intracranial operations for brain tumours, and this incidence was higher than in those undergoing no intracranial operations. 5–8 Observational investigations in patients after intracranial surgeries have been scarce.…”
Section: Introductionmentioning
confidence: 98%
“… 11 The incidence of agitation reported in our pilot study was still much higher than these results. 4 9–11 These discrepancies warrant a prospective cohort study with a large sample size to determine the precise incidence of emergence agitation in patients after intracranial surgery.…”
Section: Introductionmentioning
confidence: 99%